Theoretical and methodological foundations of the development of pilgrimage tourism in Uzbekistan - Anvar Aidjanovich Khudoyarov (Peerian Journals Publishing, 2023)
Uzbekistan attracts world scientists and tourists with its rich cultural and spiritual heritage, memorial and visual arts, historical monuments and many famous and great ancestors of ours. This, in turn, shows our unique position and influence in international tourism markets
Keywords: memorial; markets; famous; tourists